Animals and their correspondences - Benade, William Henry, 1816-1905 (Preservation and Access for American and British Children's Literature, 1850-1869 (NEH PA-23536-00), 1851)
Explains how domesticated and wild animals, insects, birds and fish of the natural world correspond to thoughts and affections in the spiritual world.